RNF43 over-expression inhibits the proliferation,migration and invasion of clear cell renal cell carcinoma cell line 786-O - SUN Zhi-chao, WANG Xiu-zhi, YANG Shu-hui, PU Yang (Jichu yixue yu linchuang, 2021)
Objective To assess RNF43 on the proliferation,migration,and invasion of clear cell renal cell carcinoma(ccRCC) cell line 786-O. Methods GEPIA website was visited to analyze RNF43 expression and perform prognosis analysis of the patients with clear cell renal cell carcinoma. RNF43 over-expressing 786-O was established by cationic transfection. Inhibitory efficiency of RNF43 over-expression and Wnt inhibitor LGK974 on 786-O cells were checked by Western blot or qPCR. The effects of RNF43 over-expression and LGK974 on cell proliferation,migration and invasion of 786-O were analyzed by CCK8,clone formation,wound healing assay and Transwell assay respectively. Results RNF43 was reduced in ccRCC tissues. Low expression was associated with poor prognosis. RNF43 over-expression or LGK974 treatment led to decreased expression of β-catenin and non-phospho (active) β-catenin in 786-O cells(P＜0.05),along with significantly reduced cell proliferation,migration,and invasion(P＜0.001). Conclusions RNF43 inhibits proliferation,migration and invasion of 786-O cells by suppressing Wnt/β-catenin pathway.